Supplier Engagement and Contract Performance: A Case Study of Mbale District Local Government - Francis Faizo Ndaula (Uganda Christian University, 2024)
The research was undertaken to investigate on influence of supplier engagement on contract performance. It was guided by three objectives; to assess the effect of procurement processes on contract performance in Mbale District Local Government, to analyze the effect of supplier selection on contract performance in Mbale District Local Government, to examine the effect of ethical standards on contract performance in Mbale District Local Government. The researcher used a sample size of 63 respondents and used questionnaires and interview guide to collect data and later the data was analyzed using the statistical package for social sciences (SPSS). Results of the first objective shows that procurement processes positively (Beta=0.153) contract performance in Mbale District Local Government predicts and effect is significant at p-value < 0.05. by 9.6%, Results of the second objective reveals that supplier selection on positively (Beta=0.224) predicts the contract performance in Mbale District Local Government and effect is significant at p-value < 0.05 by 7.7% while results of the third objective show that ethical standards (Beta=0.091) predicts and affects their contract performance in Mbale District Local Government. However, its effect is insignificant at p-value > 0.05 by 2.1%. It can be concluded that procurement processes has a significant effect on contract performance in Mbale District Local Government, supplier selection has a significant effect on contract performance in Mbale District Local Government and lastly ethical standards have a significant effect on contract performance in Mbale District Local Government. Mbale District Local Government should implement transparent and competitive bidding processes ensure fairness and selects the most capable contractors. Additionally, leveraging technology through e-procurement systems can streamline procurement activities, reduce errors, and increase efficiency.